2001
DOI: 10.2343/geochemj.35.189
|View full text |Cite
|
Sign up to set email alerts
|

C/N ratios in a sediment core from Nakaumi Lagoon, southwest Japan. Usefulness as an organic source indicator.

Abstract: The weight ratio of total organic carbon to total nitrogen (C/N ratio) in 20 meters of sediment core from Nakaumi Lagoon (coastal brackish lake), Japan is examined for its suitability as an organic source indicator. The C/N ratio depth profile is compared to the depth profiles of other proxies, i.e., weight ratio of total organic carbon to total organic nitrogen (C/N org. ratio), stanol compositions, n-alkane compositions and the hydrogen-index by Rock-Eval pyrolysis.The C/N ratios of the lagoonal sediments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(96 citation statements)
references
References 51 publications
4
86
1
5
Order By: Relevance
“…The C/N ratios of the surface sediment organics in Lake Nakaumi analyzed in this study are 7-9 at most sampling stations in the lake. Figure 4 shows that TOC has a good correlation with TN with positive slope of about 8.7, which indicates that this organic matter is derived mainly from planktic organisms (Bordowskiy 1965;Sampei and Matsumoto 2001). Lake Nakaumi is likely to be rich in planktic organics: the water depth is shallow; the lake is easily stratified and bottom water is seasonally anoxic; and both primary productivity and sedimentation rates are high (1-2 mm year -1 ; Nakano-umi and Shinji-ko Research Group et al 1987;Shinji-ko Research Group et al 1986;Sampei et al 1997a).…”
Section: Relationship Between H 2 S Concentrations and Toc Contentsmentioning
confidence: 95%
“…The C/N ratios of the surface sediment organics in Lake Nakaumi analyzed in this study are 7-9 at most sampling stations in the lake. Figure 4 shows that TOC has a good correlation with TN with positive slope of about 8.7, which indicates that this organic matter is derived mainly from planktic organisms (Bordowskiy 1965;Sampei and Matsumoto 2001). Lake Nakaumi is likely to be rich in planktic organics: the water depth is shallow; the lake is easily stratified and bottom water is seasonally anoxic; and both primary productivity and sedimentation rates are high (1-2 mm year -1 ; Nakano-umi and Shinji-ko Research Group et al 1987;Shinji-ko Research Group et al 1986;Sampei et al 1997a).…”
Section: Relationship Between H 2 S Concentrations and Toc Contentsmentioning
confidence: 95%
“…The low C/N values indicated that autochthonous organic matter most likely contributed to the sediments. It is pointed out that conventional C/N ratio (TOC/TN ratio) sometimes leads to an incorrect interpretation due to abundant inorganic nitrogen (IN) input (Sampei et al, 1997;Sampei and Matsumoto, 2001;Meyers, 2003). Plot of the TOC versus TN concentration of the RB core indicated that contribution of IN is significant in the sediments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…C/N ratio of planktonic organic matter in sedimentary environments increases with decomposition rate of the organic matter (Tissot and Welte, 1984). High cellulose and lignin composition of vascular terrestrial plants, along with low protein content, result in C/N ratio valueslarger than 15 (Meyers, 1994(Meyers, , 1997Sampei and Matsumoto, 2001). The C/N ratios in the studied coal samples are 20 (BCMCL1), 21 (BCMCL2), 19 (BCMCL3), 21 (BCMCL4), 20 (BCMCL5), 14 (BCMCL6), 19 (BCMCL7), and 16 (BCMCL8), respectively, with mean C/N ratio of 19 (Table II).…”
Section: Origin Of Organic Mattermentioning
confidence: 99%
“…Terrestrial vascular plants and their derivatives in sediments have C/N ratios of greater than 15 (Ertel and Hedges, 1984;Sampei and Matsumoto, 2001) and those of wood, leaf and macrophytee specially high at 209, 28 and 39, respectively (Hedge et al, 1986). Generally, planktonic organic matters deposited in deep-sea sediments contain C/N values higher than 10 to 15 (Müller, 1977) owing to the preferential loss of nitrogen relative to carbon (Müller, 1977).…”
Section: Origin Of Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation